1995
DOI: 10.1017/s0022112095001558
|View full text |Cite
|
Sign up to set email alerts
|

Stratified circular Couette flow: instability and flow regimes

Abstract: The stability conditions of the flow between two concentric cylinders with the inner one rotating (circular Couette flow) have been investigated experimentally and theoretically for a fluid with axial, stable linear density stratification. The behaviour of the flow, therefore, depends on the Froude number Fr = Ω/N (where Ω is the angular velocity of the inner cylinder and N is the buoyancy frequency of the fluid) in addition to the Reynolds number and the non-dimensional gap width ε, here equal to 0.275.Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 7 publications
(11 reference statements)
1
29
0
Order By: Relevance
“…2 we compare the calculated marginal stability line (i.e. (ω) = 0) for axisymmetric disturbances with experimental values by Boubnov et al (1995). The agreement is rather good except for small values of the Froude number…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…2 we compare the calculated marginal stability line (i.e. (ω) = 0) for axisymmetric disturbances with experimental values by Boubnov et al (1995). The agreement is rather good except for small values of the Froude number…”
Section: Resultsmentioning
confidence: 67%
“…Further experimental and theoretical studies by Boubnov et al (1995) and Caton et al (2000) of flows between concentric rotating cylinders with a stable axial density stratification confirmed the stabilizing role of the density stratification and showed that i) the critical Reynolds number depends on the buoyancy frequency (or Brunt-Väisälä frequency) of the fluid; and ii) the stratification reduces the vertical extension of the Taylor vortices. The numerical results of Hua et al (1997) have reproduced the experimental results.…”
Section: Introductionmentioning
confidence: 90%
“…The first experiment on stratified Taylor-Couette flow was performed by Thorpe [3] in 1966. His results were further extended by the experiments of Withjack and Chen [4], Boubnov et al [5], Caton et al [6] and by the numerical simulations of Hua et al [7]. Most of these studies were performed with a stationary outer cylinder and all concluded that stable vertical stratification stabilizes the flow and reduces the axial wavelength of the unstable modes which bifurcate through Hopf bifurcations.…”
mentioning
confidence: 91%
“…their pulsating axisymmetric modes) within the explored range, presumably because its unstable region is too narrow and our experimental device is not precise enough to excite this very marginal state (see the comparison between the results of [5] and [6]). Nevertheless, in experiments at µ = 0 and large Reynolds number, we observed the reappearance of stationary axisymmetric Taylor vortices in agreement with the regime diagram of Boubnov et al [5]. This stationary axisymmetric mode was never excited when decreasing µ for µ > 0, but once excited at µ = 0, they could then be maintained up to µ = 0.2.…”
mentioning
confidence: 97%
“…A novel bifurcation diagram is found, explaining the discrepancies between previous experimental studies [7,8] and numerical simulations [9]. The diagram enlightens the interaction between two branches and gives evidence to an unusual saddle-node transition.…”
mentioning
confidence: 51%